Collective action and property rights for sustainable development - Meinzen-Dick, Ruth S.; Di Gregorio, Monica (International Food Policy Research Institute, 2004)
Institutions of collective action and systems of property rights shape how people use natural resources, and these patterns of use in turn affect the outcomes of people’s agricultural production systems. Together, mechanisms of collective action and property rights define the incentives people face for undertaking sustainable and productive management strategies, and they affect the level and distribution of benefits from natural resources. The linkages between property rights, collective action, and natural resource management have important implications for technology adoption, economic growth, food security, poverty reduction, and environmental sustainability. Yet despite their importance in people’s lives, property rights and collective action are often undervalued, and when they are recognized, often misunderstood.